Semantics-based locking: From isolation to cooperation - Rainer Unland (Westfälische Wilhelms-Universität Münster, Institut für Wirtschaftsinformatik, 1994)
Advanced database applications, such as CAD/CAM, CASE, large AI applications or image and voice processing, place demands on transaction management which differ substantially from those of traditional database applications. In particular, there is a need to support enriched data models (which include, for example, complex objects or version and configuration management), synergistic cooperative work, and application- or user-supported consistency. This paper deals with a subset of these problems. It develops a methodology for implementing semantics-based concurrency control on the basis of ordinary locking. More specifically, it will be shown how conventional locking can step by step be improved and refined to finally reach our initial goal, namely a comprehensive support of synergistic cooperative work by the exploitation of application-specific semantics. In addition to the conventional binding of locks to transactions we consider the binding of locks to objects (object related) and subjects (subject related locks). Object related locks can define persistent and adaptable access restrictions on objects. This permits, among others, the modeling of different types of version models (time versions, version graphs) as well as library (standard) objects. Subject related locks are bound to subjects (user, application, etc.) and can be used among others to supervise or direct the transfer of objects between transactions.
Keywords: 650; transaction management; non-standard applications; semantics-based concurrency control; nested transactions; synergistic cooperative work